The Attributes Of Eco-Labels: The Sustainability Of Customer Green Behavior - Alamsyah, Doni Purnama; Othman, Norfaridatul Akmaliah; Wan Ibrahim, Nik Rahila; Wen, Yaw Danny Chung; Mulyani, Mulyani; Udjaja, Yogi (The Mattingley Publishing Co., Inc., 2020)
An Eco-label is an attribute associated with environmentally friendly products. The marketers use it widely in providing the value of products offered. Based on the phenomenon, this study aims to review the impact of eco-labels on customerM behavior that relates to green awareness, green trust, environmental knowledge, and perceived quality. This study is conducted in Indonesia, particularly in West Java, with 100 supermarket customers as research respondents. Data from the respondents is obtained through questionnaires quantitatively, and data is analyzed through SmartPLS in examining the correlation values. The research result shows that an eco-label is an attribute to a green product, and it has a correlation and positive impact on green awareness, green trust, environmental knowledge, and perceived quality from customers. The attribute of an eco-label provides a more significant impact on the green value of green awareness and green trust compared to natural values. Research findings can provide input to the marketer in taking green marketing policies through the attribute of an eco-label. For the government, it is as essential information in understanding a customer’s knowledge for the attribute of eco-labels